2017
DOI: 10.1021/acsami.6b11979
|View full text |Cite
|
Sign up to set email alerts
|

Highly Anisotropic Thermal Conductivity of Layer-by-Layer Assembled Nanofibrillated Cellulose/Graphene Nanosheets Hybrid Films for Thermal Management

Abstract: An anisotropic thermally conductive film with tailorable microstructures and macroproperties is fabricated using a layer-by-layer (LbL) assembly of graphene oxide (GO) and nanofibrillated cellulose (NFC) on a flexible NFC substrate driven by hydrogen bonding interactions, followed by chemical reduction process. The resulting NFC/reduced graphene oxide (RGO) hybrid film reveals an orderly hierarchical structure in which the RGO nanosheets exhibit a high degree of orientation along the in-plane direction. The as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
188
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(191 citation statements)
references
References 75 publications
3
188
0
Order By: Relevance
“…A series of studies investigated paper‐based TIMs with cellulose in composite with functionalized graphene. Song et al integrated nanofibrillated cellulose and graphene nanosheets for thermal management . Jeon and coworkers also studied the interaction between graphene and cellulose by varying six types of commercially available paper for TIMs fabrication.…”
Section: Carbon Allotrope Materials In Tims Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies investigated paper‐based TIMs with cellulose in composite with functionalized graphene. Song et al integrated nanofibrillated cellulose and graphene nanosheets for thermal management . Jeon and coworkers also studied the interaction between graphene and cellulose by varying six types of commercially available paper for TIMs fabrication.…”
Section: Carbon Allotrope Materials In Tims Applicationmentioning
confidence: 99%
“…Song et al integrated nanofibrillated cellulose and graphene nanosheets for thermal management. [105][106][107] Jeon and coworkers also studied the interaction between graphene and cellulose by varying six types of commercially available paper for TIMs fabrication. They found that the thermal conductivity of the in-plane graphene-coated paper is 6.78 W (m K) −1 , and that of bare paper is 0.05 W (m K) −1 .…”
Section: Graphenementioning
confidence: 99%
“…CNCs have significant mechanical strength, aeolotropism, and elasticity because of their highly well‐aligned layering. Over the past decade, it has attracted wide attention in the fields of tissue engineering and material engineering . Huang et al prepared silk fibroin nanofiber membrane enhanced with CNCs by electrospinning; the tensile strength of these membranes were almost two times that of non‐reinforced silk fibroin nanofiber membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity is obtained by the formula: K ¼ a  r  C p , where a is the thermal diffusivity, r is the mass density and C p is the specic heat of the sample. The detailed mechanism and methodology of the laser ash system have ever been reported in our previous study 27,28 ( Fig. S2 †).…”
Section: Tc Of Pg Compositesmentioning
confidence: 99%